Peran Zainuddin Labay El Yunusy dalam Pembaruan Pendidikan Islam di Indonesia - Bagas Mangku Prasetyo; Fajar Abi Pangestu; Reival Miftahul Fathir Nugroho (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This research aims to analyze the contributions and thoughts of Zainuddin Labay El Yunusy toward the transformation of the Islamic education system in Indonesia during the early 20th century. As a central figure from Padang Panjang, West Sumatra, he pioneered a paradigm shift from the traditional halaqah education system to a more structured classical system through the establishment of Diniyyah School in 1915. The method used in this study is a descriptive-analytical historical method with a literature review approach. The findings indicate that the reforms initiated by Zainuddin Labay encompassed the integration of a curriculum that combined religious sciences with general subjects, the adoption of modern teaching methodologies such as the classroom system and formal school infrastructure and institutional modernization that inspired the birth of various modern madrasahs across the archipelago. Zainuddin Labay’s visionary steps not only broke the stagnation of Islamic education at the time but also successfully laid the foundation for a madrasah system that remains adaptive to contemporary demands while remaining deeply rooted in strong Islamic values.